Nomograms for Predicting Overall Survival and Cancer-Specific Survival of Patients With Renal Cell Carcinoma and Venous Tumor Thrombus: A Population-Based Study - Yang, Lin; Fu, Bin (Frontiers in Surgery, 2022)
Background To provide better prognostic information for patients with renal cell carcinoma (RCC) combined with venous tumor thrombus (VTT). In turn, guide patients’ families and doctors to formulate plans for follow-up treatment and follow-up. We developed nomograms to predict cancer-specific survival (CSS) and overall survival (OS). Methods A total of 2961 cases were included in this study. Through univariate and multivariate Cox proportional hazard regression analysis, independent risk factors affecting CSS and OS were screened out, and then a nomogram was drawn based on the screened variables. Results Independent risk factors affecting CSS include: tumor size (HR = 1.05), histology (HR = 1.75), grade (HR = 1.94), N staging (HR = 2.06), and M staging (HR = 2.87). The median survival time for CSS was 106 months. Independent risk factors for OS include age (HR = 1.60), tumor size (HR = 1.04), histology (HR = 1.60), grade (HR = 1.68), N staging (HR-1.99), M staging (HR = 2.45). The median survival time for OS is 67 months. Conclusions The nomogram based on independent risk factors affecting CSS and OS can well predict the prognosis of renal cell carcinoma with venous tumor thrombus.